Comparative Analysis of the Physicochemical and Microbiological Properties of Lactobacillus plantarum and Lactobacillus acidophilus Fermented Milk with Prebiotic Kepok Banana (Musa acuminata × balbisiana) - Windari, Trisna; Yurliasni, Yurliasni; Mariana, Elmy; Marpaung, Deva Aryana; Jinnani, Rida Raihatil (CV. Science Tech Group, 2025)
Probiotics are microbes that are alive and beneficial to their hosts. Some probiotic bacteria are Lactobacillus plantarum and Lactobacillus acidhopillus. The performance of these two bacteria will be optimal if prebiotics are added as a source of nutrition, namely kepok banana (Musa acuminata × balbisiana). The aim of the research was to analyze the comparative physicochemical and microbiological properties of fermented goat's milk using Lactobacillus plantarum and Lactobacillus acidhopillus with prebiotic kepok banana puree (Musa acuminata × balbisiana). The study used a completely randomized design with a factorial pattern, factor A percentage of kepok banana puree P1= 5% kepok banana puree, and P2= 15% kepok banana puree, factor B V1= Lactobacillus plantarum (5%) and V1= Lactobacillus acidhopillus ( 5%), done 3 times repetition. The results of the research were that adding 15% kepok banana puree to Lactobacillus plantarum was better at increasing lactic acid levels and bacterial growth in the Total Plate Count, and 15% kepok banana puree to Lactobacillus acidophilus was better at lowering pH, increasing protein levels, reducing syneresis and increase the viscosity value. The conclusion of this research is that the use of 15% can improve the performance of Lactobacillus plantarum and Lactobacillus acidhopillus, and in general all research parameters are still within the Indonesian National Standard range. These findings contribute to the advancement of food science and microbiology by demonstrating the potential of kepok banana puree in improving the quality of goat milk-based probiotic products.